(untitled) (Research, Society and Development, 2021)
This article aims to analyze the emergence of educational institutions in the historical context of the Vila da Paz, in Teresina-PI, community, through the analysis of the socio-educational performance of Pedro Balzi, a priest who marked his priesthood in missionary actions, among which the building schools. The research sought to understand how the implementation of educational establishments contributed to changes in the scenario of the Village. It was identified that the actions of the clergyman, especially in the educational aspect, assumed a prominent position for the historical configuration of the Vila. Located in the south of Teresina, the object is inserted in the 1980 to 1990 section, taking as a starting point of the analysis the social context of the capital in the eighties, marked by irregular occupations in the urban fabric. From these clippings, it was found that the work developed by Father Balzi, mainly through the construction of schools, became the mobilizing agent of the first urbanization actions in Vila da Paz, changing the urban fabric of the city and the daily lives of its residents. residents. Along this path, we sought to establish interlocutions with the writings of Scott Mainwaring, Ana Fani Alessandri Carlos, Maurice Halbwachs, among others. As a documentary backing, the research was based on bibliographic, hemerographic and oral reports.